Has family involvement migrated into higher education? An investigation of how administrative staff document the phenomenon in students' university experiences in Cyprus. Issue 1 (2nd January 2018) - Symeou, Loizos; Theodorou, Eleni; Lamprianou, Iasonas; Rentzou, Konstantina; Andreou, Panayiota
Abstract: Families have been getting more and more involved in their children's education. This paper presents findings of a study investigating family involvement in their members' undergraduate studies attending a state (non-fee-paying) and a private (fee-paying) university in Cyprus. The data presented in the paper were collected via online logs completed by administrative personnel in the two universities documenting incidents of family involvement. The data analysis demonstrates how similarly the phenomenon manifests in both universities and suggests that where the two universities differ is more in the intensity of the various modes of family involvement. It also projects students' desires and encouragement of their family's involvement and their families' intervention to protect or guide them. The findings of the study are discussed in view of cultural and societal norms and changes about parenthood and the relationship between families and their university age members in a marketized higher education context.